Information-processing, technological progress and regional retail networks dynamics - Jacek Cukrowski (European Regional Science Association (ERSA), 1998)
In underdeveloped regions retail firms play a significant role in employment creation and provide local governments with large part of their tax revenues. The existence of retail networks is usually explained by spatial factors and economies of scale in transportation and/or increasing returns in storage. In many cases, such as trade in services or goods that cannot be transported or stored, these factors are irrelevant. The hypothesis in the paper is that the existence of retail networks can be explained by the rational behaviour of firms operating in a stochastic environment. It is shown that demand uncertainty serves as an independent source of retail trade, and, consequently, the ability of firms to process information and predict demand affects the characteristics of retail networks. The results indicate that (1) risk-averse firms always devote resources to demand forecasting, (2)producers are better off trading with retailers than with final consumers, (3) the volume of output supplied through the retail network is greater than it would be if producers traded directly with consumers (it improves welfare), (4) the size of retail networks is determined by the variance of demand fluctuations, (5) technological progress in data-processing, which decreases uncertainty about demand, also decreases the size of retail networks. This, in turn,reduces employment and tax revenues in underdeveloped regions.
Keywords: 330